2022
DOI: 10.1371/journal.pone.0273748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accuracy and performance of self-reported HIV and antiretroviral therapy status in the Nigeria AIDS Indicator and Impact Survey (2018)

Abstract: Background Data on awareness of HIV status among people living with HIV (PLHIV) are critical to estimating progress toward epidemic control. To ascertain the accuracy of self-reported HIV status and antiretroviral drug (ARV) use in the Nigeria HIV/AIDS Indicator and Impact Survey (NAIIS), we compared self-reported HIV status with HIV rapid diagnostic test (RDT) results and self-reported ARV use with detectable blood ARV levels. Methods On the basis of responses and test results, participants were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, this proportion is smaller than several other studies that report up to 10% of discordancy between self-report and HIV-positive status. 7,8,12 Various factors may contribute to this discordancy which include (1) wrong self-report of HIV status, (2) initial false-positive HIV diagnosis, or (3) misunderstanding of the questionnaire resulting in wrong response during the survey. Although HIV diagnostic tests are highly reliable and accurate, studies have reported false-positive HIV diagnoses in all settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this proportion is smaller than several other studies that report up to 10% of discordancy between self-report and HIV-positive status. 7,8,12 Various factors may contribute to this discordancy which include (1) wrong self-report of HIV status, (2) initial false-positive HIV diagnosis, or (3) misunderstanding of the questionnaire resulting in wrong response during the survey. Although HIV diagnostic tests are highly reliable and accurate, studies have reported false-positive HIV diagnoses in all settings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ibrahim and colleagues reported positive predictive value of 92% for self-reported HIV-positive status in a large HIV-focused survey in Nigeria. 7…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…127 The low self-reported ART coverage among people who knew their status (15-25%) is in sharp contrast to the estimated 91% 18 coverage among the Zimbabwean general population, 67% among FSW, 36 45% among MSM 45 and 34% among transgender women. 45 While the accuracy of self-reported ART status can vary greatly and is often subject to quite extreme under reporting in surveys, 47,48 misreporting ART use within the context of a programme is likely much less as it results in immediate and supported linkage to ART.…”
Section: Discussionmentioning
confidence: 99%